Calidad de alimentación, satisfacción de desayuno escolar y rendimiento académico de los estudiantes del nivel primario de la I.E.P.S.M. Nº601331 13 de Febrero – San Juan Bautista, 2023 - Valdez López, José Enrique (2024)
The aim of this study was to explore the connection between the quality of food and satisfaction of school breakfast with the academic performance of primary level students at the I.E.P.S.M. Nº601331 February 13 – San Juan Bautista. The study had a correlational, non-experimental approach, quantitative and cross-sectional approach. The methodological design was observational, descriptive in nature. The sampling was stratified probabilistic. The sample was made up of 103 students. The food consumption frequency questionnaire, user satisfaction questionnaire and students' final grade average evaluation sheet were used. This research shows that second grade primary school students have a poor academic performance of 13.04% in mathematics and communication, and we also found a poor performance in the area of science and technology of 8.70%. In terms of satisfaction with school breakfast, we have the fifth and third grades with the highest percentage of never being satisfied, 33.04% and 17.27%. In the quality of diet, 23.23% presented a healthy diet, 25.20% classified it as unhealthy and 51.57% needed changes in their diet. Concluding that there is a significant statistical relationship between the variables quality of food and user satisfaction with academic performance in the areas of mathematics, communication and science and technology.